Social Engineering and Inter-Device Eavesdropping Using SCRCPY for Spoofing and Sniffing - Wijaya, Anne Ivena; Damayanti, Yeni Rosa; Lestiani, Dwi Indah; Sugiono, Adinda Ayu Putri; Huanggino, Sherissa Callista; Rijal, Demas Muhammad; Dewi, Renny Sari (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The rapid development of technology opens up new avenues for cybercriminals to carry out acts of social engineering and eavesdropping between devices. Social engineering refers to manipulation, influence, or deception used to gain control of a computer system. This technique is utilized by cybercriminals to steal sensitive information from their victims. This research focuses on analyzing social engineering and eavesdropping techniques between devices using SCRCPY, an Android screen control tool that allows remote control of Android devices from a computer. SCRCPY presents new opportunities for cybercriminals to launch spoofing and sniffing attacks, two common techniques used in social engineering attacks. This research explores various eavesdropping scenarios, analyzing interactions between devices and users, as well as security system responses to suspicious activity. The results show that SCRCPY can be used for various social engineering and eavesdropping attacks. Cybercriminals can use SCRCPY to gain control of a victim's Android device through the perpetrator's desktop computer. These findings indicate that social engineering attacks and eavesdropping between devices are becoming increasingly sophisticated and difficult to detect. Therefore, users need to increase their awareness of these risks and take steps to protect themselves. Keywords: Social engineering, SCRCPY, spoofing, sniffing, device security.